2006
DOI: 10.13031/2013.21222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind Speed and Pressure on Linear Move Irrigation System Uniformity

Abstract: Use of center pivot and linear move sprinkler irrigation systems is becoming popular in the Southeastern United States. As these systems are used to irrigate increasing acreage, quantitative data are needed on sprinkler performance under local conditions. Two types of low pressure sprinkler nozzles were tested under field conditions, stationary grooved plate (LDN) and off-center wobbling diffuser sprinklers (IWOB). Replicated uniformity measurements were conducted along the axis of a linear move irrigation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Also, it could be noted that wind direction tended to cause little influence on CU and DU values. However, it was found that the greater was the wind speed, the lesser were the uniformity coefficients (CU and DU), corroborating with TARJUELO et al (1992) and DUKES (2006).…”
Section: Resultssupporting
confidence: 61%
“…Also, it could be noted that wind direction tended to cause little influence on CU and DU values. However, it was found that the greater was the wind speed, the lesser were the uniformity coefficients (CU and DU), corroborating with TARJUELO et al (1992) and DUKES (2006).…”
Section: Resultssupporting
confidence: 61%
“…The hourly reference evapotranspiration was more intense for assessments 7, 8, and 9 (ETo = 0.67 mm h −1 ), when the relative air humidity (RH) was low and vapor pressure deficit values (∆e) and wind speed at 2 m high (u 2 ) were relatively high. According to Dukes (2006), u 2 values lower than 1.7 m s −1 are classified as low. Thus, u 2 values were low in tests 1, 2, 3, 7, 8, and 9 and high in tests 4, 5, and 6 (Table 3).…”
Section: ∆ S (T) − [Rh × S (T)]mentioning
confidence: 99%
“…Furthermore, the influence of wind on the sprinkler intensity uniformity of sprinkler irrigation systems composed of multiple sprinklers and represented by laterally-moving sprinkler irrigation systems is not significant. This was due to the superposition of the distribution of sprinkler intensity of multiple sprinklers, which reduces the influence of wind on the sprinkler intensity uniformity of sprinkler irrigation systems [30,[46][47][48][49][50][51][52]. At present, the relevant research is concerned with using constant water pressure to carry out experiments.…”
Section: Discussionmentioning
confidence: 99%